Peningkatan Pengetahuan dan Perilaku untuk Mencegah Skoliosis pada Siswa Sekolah Dasar SDN 3 Pandanwangi Melalui Edukasi Postur Tubuh - Fiona Amalia Diandara Khinayah; Zidni Imanurrohmah Lubis; Fika Ertitri (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Elementary school-aged children are in a period of rapid growth and are therefore susceptible to postural disorders, including scoliosis. Risk factors such as incorrect sitting posture, unbalanced bag carrying habits, and lack of physical activity can be prevented through early posture education. This community service activity was held on Monday, September 22, 2025, at SDN Pandanwangi 3, involving 448 students in grades 1–6. The methods used included interactive material delivery, posture demonstrations, movement simulations, and evaluation through quiz games and posture challenges. The results showed high student enthusiasm, with more than 80% able to answer questions and demonstrate correct posture, although lower-grade students still needed guidance. Physiotherapy-based education has been proven effective in improving students' knowledge and skills in maintaining posture, so it is important to carry it out continuously with the support of teachers and parents to prevent scoliosis from an early age. The results demonstrated positive outcomes, with over 80% of students able to correctly answer questions and perform posture exercises. The initiative underscores the importance of ongoing physiotherapy-based education, supported by both teachers and parents, in fostering good posture habits among young students.